The MUSE view of the Sculptor galaxy: Survey overview and the luminosity function of planetary nebulae - Congiu, E.; Scheuermann, F.; Kreckel, K.; Leroy, A.; Emsellem, E.; Belfiore, F.; Hartke, J.; Anand, G.; Egorov, O. V.; Groves, B.; Kravtsov, T.; Thilker, D.; et al. (EDP SCIENCES S A, 2026)
The Sculptor galaxy, NGC 253, is the southern massive star-forming disk galaxy that is closest to the Milky Way. We present a new 103-pointing MUSE mosaic of this galaxy that covers most of its star-forming disk up to 0.75 x R-25. With an area of similar to 20 x 5 arcmin(2) (similar to 20 x 5 kpc(2), projected) and a physical resolution of similar to 15 pc, this mosaic constitutes one of the largest integral field spectroscopy surveys with the highest physical resolution of any star-forming galaxy to date. We exploited the mosaic to identify a sample of similar to 500 planetary nebulae (the sample is similar to 20 times larger than in previous studies) to build the planetary nebula luminosity function (PNLF) and obtain a new estimate of the distance to NGC 253. The value we obtained is 17% higher than the estimates returned by other reliable measurements, which were mainly obtained via the top of the red giant branch method. The PNLF also varies between the centre (r < 4 kpc) and the disk of the galaxy. The distance derived from the PNLF of the outer disk is comparable to that of the full sample, while the PNLF of the centre returns a distance that is larger by similar to 0.9 Mpc. Our analysis suggests that extinction related to the dust-rich interstellar medium and edge-on view of the galaxy (the average E(B-V) across the disk is similar to 0.35 mag) plays a major role in explaining both the larger distance recovered from the full PNLF and the difference between the PNLFs in the centre and the disk.